Contribuição das tecnologias da informação e comunicação (tics) para a acessibilidade de pessoas com deficiência visual: o caso da Universidade Federal do Ceará - Juvêncio, Vera Lúcia Pontes (2013)
This study points to access, permanence and autonomy of people with visual impairment, poor vision or total blindness, with the use of information and communication technologies (ICTs), the informatics and its augmentation with communication capabilities, as tools of interaction with environments found at the Federal University of Ceará (UFC). We present a theoretical framework of the issue through the following topics: special education and inclusive education, assistive technology, visual impairment, the legal system, including higher education, the use of ICT, usability and ergonomics, accessibility and inclusion, universal design, web accessibility, programs with speech synthesizers, building websites for full development to make them accessible to the visually impaired, as well as the accessibility at the Federal University of Ceará. The methodology was exploratory, descriptive, and application of instruments: questionnaires, interviews and tests, people with visual impairments that make up the university community, students and employees. The questionnaire was sent via internet and a visit for the interview and testing was scheduled by e-mail, phone or in person. The answers to the questionnaires for data collection were sent by e-mail. The research was conducted with eight people, one teacher and seven students, all totally blind or with poor vision. In the chapter on Methodology, besides addressing the collecting, processing and data analysis technique, details of the research are also provided. The results address the life course of the research subjects and the perception of these people in relation to accessibility in UFC. In addition, the specific objectives and analysis of results were also verified. A list of recommendations was then released.